Kualitas Pelayanan Pembuatan KTP-elektronik Pada Dinas Kependudukan dan Pencatatan Sipil Kota Bogor - Dinillah, Kunco; Hermawan, Denny; Munjin, R. Akhmad (Universitas Djuanda, 2019)
This study aims to determine how the Quality of KTP-el Service Making in the Population and Civil Registration Office of Bogor City. The increasing need in various lines of life and the need for documents of every citizen is a must. The service provided by the government to the public is to serve the State Administration, namely taking care of the official identity that must be owned by every citizen who is domiciled in Indonesia. The method used in this research is a descriptive method that is a description in the form of a description to explain the answers given by respondents in the questionnaire, the data obtained through interviews, literature studies and observations. The results of this study indicate that the quality of KTP-el services at the Department of Population and Civil Registration of Bogor City according to respondents is included in the criteria quite well. This is explained that the completion of KTP-el services is not optimal in terms of speed in printing which must wait for blanks from the center to inadequate facilities, the unavailability of benches to accommodate the public and the attitude of officers towards people who are not friendly to the community.